Responsibility and freedom : the ethical realm of RRI - Gianni, Robert (London, UK : ISTE, Ltd. ; Hoboken, NJ : John Wiley & Sons, 2016)
Responsible Research and Innovation appears as a paradoxical frame, hard to conceptualize and difficult to apply. If on the one hand research and innovation appear to follow logics blind to societal issues, responsibility is still a blurred concept interpreted according to circumstances. Different perspectives are implied in the RRI discourse rendering difficult also its application, because each social dimension proposes a different path for its implementation. This book will try to indicate how such conflictual understanding of RRI is caused by a reductive interpretation of ethics and, consequently, of responsibility. The resulting framework will represent an ethical approach to RRI that could help in overcoming conflictual perspectives and construct a multi-layer approach to research and innovation.
Responsible Research and Innovation: A New Framework for an Old Controversy / Robert Gianni -- Responsibility: A Modern Concept / Robert Gianni -- Development of Freedom / Robert Gianni -- An Ethical Perspective on Responsibility and Freedom / Robert Gianni -- Framework for the Ethical Assessment of RRI / Robert Gianni -- Conclusion.
Online resource; title from PDF title page (John Wiley, viewed February 19, 2016).
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Research -- Moral and ethical aspects; Ethics, Research; Recherche -- Aspect moral; BUSINESS & ECONOMICS -- Business Ethics; Research -- Moral and ethical aspects